Female re-victimization in journalistic articles on femicide in Mexico - Flores Treviño, María Eugenia (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Language constructs and deconstructs people; it represents and projects its ethos and its social image, and as in this study, it can doubly violate the victims. Therefore, the management of journalistic discourse is a determining factor in the construction of the socio-discursive image of women who have been victims in cases of femicide in several states of Mexico. Gender-based violence is a phenomenon that suffocates society; and it is crossed by other geographical and socio-contextual factors in some events registered among the Mexican population. In this work, 5 cases of femicide and their narratives are reviewed -out of a corpus of 12- that were documented in the national and international press, to find the discursive patterns and resources and strategies in the linguistic actions related to the construction of the social image of the victim. With a methodology based on pragmatics and sociopragmatics as well as Critical Discourse Analysis, the publications produced on these cases that occurred between 2022 and 2023 are examined. Among the main trends is that the editors resort to sexist stereotypes regarding the actions or behaviors of the female victims.
Keywords: revictimization; discourse; femicide; Mexico